2010
DOI: 10.1007/s11274-010-0410-y
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal activity of Trichoderma spp. and isolation of an active compound

Abstract: Trichoderma spp. play an important role in biotic control, and several are efficacious against nematodes. To study the potential of Trichoderma species in controlling nematodes, fungal filtrates of 329 Trichoderma strains were evaluated for their nematicidal activity against Panagrellus redivivus and Caenorhabditis elegans. Fifteen strains exhibited nematicidal activity against P. redivivus, and 14 strains showed activity against C. elegans. The strain YMF1.02647 showed strong nematicidal activity against both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Compounds 1 and 5-12 were dissolved in methanol and then diluted to different concentrations (400 and 200 ppm) with sterile water. The nematicidal activity against C. elegans was assayed according to the method based on references [31,32].…”
Section: Nematicidal Activitymentioning
confidence: 99%
“…Compounds 1 and 5-12 were dissolved in methanol and then diluted to different concentrations (400 and 200 ppm) with sterile water. The nematicidal activity against C. elegans was assayed according to the method based on references [31,32].…”
Section: Nematicidal Activitymentioning
confidence: 99%
“…However, the genus Trichoderma also has potential to control plant-parasitic nematodes (Sahebani and Hadavi, 2008;Yang et al, 2010). Simultaneously, several reports have indicated that T. harzianum induced systemic resistance in the plant challenged with fungal and bacterial pathogens (Harman et al, 2004;Singh et al, 2016a, b).…”
Section: Research Articlementioning
confidence: 99%
“…Many studies demonstrated that Trichoderma spp. can inhibit growth or kill soil borne pathogens and revealed different antagonistic interactions between the antagonist Trichoderma and the pathogen in vitro and in vivo (Lumsden et al, 1993;Monte, 2001;Yang et al, 2010). Actually, few research work have focused on the biocontrol efficacy of Trichoderma spp against Verticillium in vivo though important antagonistic potential were involved against Verticillium dahliae when in vitro assays were applied.…”
Section: Introductionmentioning
confidence: 99%